Sub - Hepatic Fibrome - Perrier, José P; Piñeyro, Alberto; Bergalli, Luis (Cirugía del Uruguay, 1981)
Report of an unusual abdominal tumor, with respect to which no prior bibliographic reference has been found. The paper includes review of the problem presented by the diagnosis of large abdominal turnors and the fact that only the anatomopathologic udy of piece can determine its nature.